2015
DOI: 10.1016/j.joca.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of cartilage degeneration with four year weight gain – 3T MRI data from the Osteoarthritis Initiative

Abstract: Objective To determine the effect of weight gain on progression of early knee morphologic abnormalities using magnetic resonance imaging (MRI) in a longitudinal study over 48 months. Design We studied the right knee of 100 subjects from the Osteoarthritis Initiative, selecting subjects aged ≥ 45 with osteoarthritis risk factors who demonstrated weight gain (minimum 5% increase in body mass index, BMI, n=50) or no change in weight (BMI change < 2%, n=50), frequency matched for age, gender, and baseline BMI. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 35 publications
0
56
1
Order By: Relevance
“…Moreover, our study was a retrospective analysis of the weight loss of participants included in the OAI, and analyses did not consider methods and weight loss regimens used, including diet, exercise, or bariatric surgery. This is a major limitation of our study and may have introduced confounding effects into our analysis that cannot be estimated because different regimens may have different effects on joint structures (eg, cartilage health might develop differently in participants starting a rigorous exercise training program compared with participants undergoing bariatric effect in patients with weight gain (18). However, given the inconsistency in the previous literature, caution is needed in estimating the clinical relevance of associations between weight loss and MR findings over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our study was a retrospective analysis of the weight loss of participants included in the OAI, and analyses did not consider methods and weight loss regimens used, including diet, exercise, or bariatric surgery. This is a major limitation of our study and may have introduced confounding effects into our analysis that cannot be estimated because different regimens may have different effects on joint structures (eg, cartilage health might develop differently in participants starting a rigorous exercise training program compared with participants undergoing bariatric effect in patients with weight gain (18). However, given the inconsistency in the previous literature, caution is needed in estimating the clinical relevance of associations between weight loss and MR findings over time.…”
Section: Discussionmentioning
confidence: 99%
“…Complete BMI data for baseline and 12-, 24-, and 48-month follow-up were available for 4526 study participants. Of those, we excluded participants with a baseline Kellgren-Lawrence score higher than 3 in the right knee, associated with exacerbation of knee joint degeneration, especially with worsening cartilage and meniscal degeneration over 48 months, when compared with stable weight (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete baseline and follow-up patellofemoral WORMS readings were available for the right knees of a sample of 443 of these potentially eligible subjects previously obtained by our group for several NIH-funded studies (Fig. 1) [22][23][24][25][26][27][28]. To minimize any potential influence caused by abnormalities of the extensor mechanism, and especially the quadriceps tendon in addition to inflammatory processes leading to effusion-synovitis, subjects showing these findings at baseline (extensor mechanism, n = 7; effusion-synovitis, n = 10) were excluded.…”
Section: Database and Subjectsmentioning
confidence: 99%
“…Epidemiologic studies have shown that focal cartilage lesions progress over time and that obesity and high-impact physical activities are associated with cartilage degeneration [10,11]. Lifestyle changes have a significant influence on disease progression [12], and early detection of cartilage damage and patient education therefore may delay hip replacement.…”
Section: Preventionmentioning
confidence: 99%